THE RELATIONSHIP BETWEEN FAMILY AND PEER SUPPORT WITH SMOKING BEHAVIOR OF ADOLESCENT BOYS IN THE WORKING AREA OF THE SUNGAI LIMAU IN YEAR 2024 - PERMAISURI, ELLA; AMELIATI, SRI; ANDRIANI, LINDA (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
Smoking is one of the problems that has not been solved from the past until now and has hit various circles of society, both adolescents and adults, where starting from elementary school, junior high school, to high school children, parents, men. From the data of the Padang Pariaman Regency Health Office, the behavior of adolescent boys who smoke is number 3 in the Sungai Limau Health Center as many as 2,063. The purpose of this study is: To determine the relationship between family and peer support and adolescent boys' smoking behavior in the working area of the Sungai Limau Health Center in 2024. This type of analytical descriptive research with a research design using a Cross Sectional approach, This research has been carried out in the working area of the Sungai Limau Health Center from July 22 to August 06, 2024. Sampling was carried out using the Random sampling technique with a sample of 44 respondents. Data collection tools are carried out using questionnaires filled out by researchers, and data processing is carried out by a computerized system. Based on the results of the research obtained, there is a relationship between family support and adolescent boys' smoking behavior, it is known that out of 44 respondents there are moderate smoking behaviors that are quite supportive (62.9%). Based on the results of the above test, data was obtained that there was a relationship between family support and smoking behavior with a p value = 0.029 < 0.05. Based on the results of the above test, there is a meaningful relationship between peers and smoking behavior with a niali p value = 0.013 < 0.05. Respondents should pay more attention to their health to avoid various diseases such as heart, stroke, and so on.